Perawatan Kecantikan Perempuan Dalam Rukmini Tatwa (Kajian Filosofi) - Ni Putu Ayu Desi Wulandari (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2021)
Rukmini Tatwa is a lontar script about the use of plant diversity to maintain fitness. and Rukmini Tatwa is a text that examines women's beauty care. How to care for women's beauty in Rukmini Tatwa consists of: 1) Virginity as the essence of beauty consisting of: virginity recipes using cream, virginity recipes using powder and virginity recipes using oil, 2) Skin care recipes in Rukmini Tatwa, 3) Recipe for female genital care in Rukmini Tatwa and 4) Recipe for having a healthy body and long life in Rukmini Tatwa. The philosophical meanings of the discourse on beauty contained in Rukmini Tatwa include; 1) The meaning of medicine and care because of the importance of knowledge about medicine and self-care for women for themselves as well as maintaining the continuity of the harmony of the household itself, 2) The meaning of preserving herbal plants because of the importance of caring for the environment and 3) Economic meaning that has a positive impact on community economy and provide business opportunities for the community, especially practitioners of herbal medicine world.Keywords: Care, Beauty, Rukmini Tatwa